PHYTOTHERAPY OF COUGH IN CHILDREN - O.A. Danilyuk ("Paediatrician" Publishers LLC, 2008)
Characteristics of treatment of cough in children with herbal medications are presented in this article. Poly therapeutic effect of medicinal plants, its high biological activity, relatively low toxicity and wide therapeutic index explain a need of phyto therapy use in treatment of cough. Advantages of phyto therapy are described, children's doses, ways of application of herbal extracts are given. The use of plants depending on the stage of disease and principles of combination of herbal medications during treatment are described.Key words: phyto therapy, cough, medicinal plants.